Human papillomavirus and oropharyngeal squamous cell carcinoma: a 12-year retrospective review in a New South Wales tertiary referral centre - Taylor, Alon; Eade, Thomas; Veivers, David; Gill, Anthony J.; Pang, Leo (Australian Journal of Otolaryngology; Vol 2 (January 2019): Australian Journal of Otolaryngology, 2019)
Background: To compare the epidemiology and survival outcomes of Australian patients with HPV-positive and -negative oropharyngeal squamous cell carcinoma (OPSCC) using a standalone p16 approach. Methods: A retrospective analysis of medical record data was performed for patients presenting with OPSCC to Royal North Shore Hospital in Sydney, Australia from 2005 to 2017. p16 immunohistochemistry (IHC) was used as a biomarker for HPV status. Epidemiological trends and clinicopathological details were compared between the HPV-positive and -negative cohorts. Three-year overall survival rates and the hazard ratio conferred by HPV positivity were calculated. Results: A total of 244 patients were included with 202 (82.8%) having HPV-positive disease. The yearly incidence of HPV-positive OPSCC increased from 2005 to 2016 (P